2017
DOI: 10.4269/ajtmh.15-0877
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Symptomatic Case of Hymenolepis diminuta Infection in an Urban-Dwelling Adult in Malaysia

Abstract: A case of infection in a 43-year-old Malaysian male with persistent abdominal colicky pain is reported. Endoscopy revealed whitish worms in the lumen of the small intestine, which were identified as after microscopy. Patient was successfully treated with a single dose of praziquantel (25 mg/kg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Humans become infected by the accidental ingestion of intermediate host such as fleas, flour beetles and other insects commonly found in grain and cereal containing the cysticercoid larvae. Infection resulting from incidental ingestion of the infective stage are often asymptomatic but heavy infection can result in persistent abdominal pain, diarrhea and anorexia (Ahmad et al., 2017; Alvarez-Fernandez et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Humans become infected by the accidental ingestion of intermediate host such as fleas, flour beetles and other insects commonly found in grain and cereal containing the cysticercoid larvae. Infection resulting from incidental ingestion of the infective stage are often asymptomatic but heavy infection can result in persistent abdominal pain, diarrhea and anorexia (Ahmad et al., 2017; Alvarez-Fernandez et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reports of worldwide studies of various populations have shown the level of occurrence of H. diminuta in faecal samples is about 0.001-5.5%. There have been reports of infections in people, in Indonesia, Thailand, the USA, the Democratic Republic of São Tomé and Principe, Italy, Spain, Turkey, Jamaica, Iran, Malaysia, as well as in Poland -Table 1 [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57].…”
Section: Epidemiologymentioning
confidence: 99%
“…More than 2,000 insect species are considered edible and constitute a source of not only protein but also vitamins and iron [60]. In the last 10 years, the presence of H. diminuta eggs in faecal samples has been identified worldwide: a 2-year--old girl in 2011 and a 43-year-old man in 2013 from Selangor (Malaysia), a 20-month-old boy from Turkey in 2015, and in 15-month-old boy from Iran in 2017 [36,51,56,57]. The epidemiological data from Iran also show an increasing trend of reported cases of hymenolepiasis: in 1986 in a 10-year-old boy, in 1972 5 cases including 4 children aged 6-11, and…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Su nombre científico se debe a que además de tener aspectos biológicos similares, los adultos se pueden confundir morfológicamente con T. castaneum, que es originaria de la India y también posee una distribución mundial; ambas especies se distribuyen simpátricamente, y constituyen plagas importantes de productos alimenticios almacenados (e.g. granos, harinas y cereales) (Halstead 1986;Campbell et al 2004), pudiendo ser transportadoras de agentes patógenos como helmintos intestinales (Hymenolepis nana) (Ahmad et al 2017), hongos productores de micotoxinas (Ascomycota: Aspergillus, Fusarium, Penicillium) (Yun et al 2018) y/o enterobacterias (Salmonella enterica, Campylobacter jejuni) (Russell et al 2013). Son también fuente de alérgenos (Alanko et al 2000) y productores de benzoquinonas, que son sustancias potencialmente cancerígenas, citotoxicolóficas e inmunotóxicas (łis et al 2011).…”
Section: Introductionunclassified